2020
DOI: 10.3389/fonc.2020.01721
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Significance of SIRT2 in Malignancies: A Tumor Suppressor or an Oncogene?

Abstract: Sirtuin 2 (SIRT2) is a member of the sirtuin protein family. It is a Class III histone deacetylase (HDACs) and predominantly localized to the cytosol. SIRT2 deacetylates histones and a number of non-histone proteins and plays a pivotal role in various physiologic processes. Previously, SIRT2 has been considered indispensable during carcinogenesis; however, there is now a significant controversy regarding whether SIRT2 is an oncogene or a tumor suppressor. The purpose of this review is to summarize the physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 80 publications
0
33
0
1
Order By: Relevance
“…Currently, the literature supports diverging functions for SIRT2 in tumorigenesis, in a context-dependent manner, that act to modify epigenetic pathways implicated in cancer’s initiation, promotion, and progression 44 46 . Our findings illustrate the novel capacity of SIRT2 to enhance subcutaneous melanoma progression while raising the vital question of at what point does SIRT2, a tumor suppressor protein that promotes genomic integrity in healthy cells, transition into what can only be described as a tumor promoter.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the literature supports diverging functions for SIRT2 in tumorigenesis, in a context-dependent manner, that act to modify epigenetic pathways implicated in cancer’s initiation, promotion, and progression 44 46 . Our findings illustrate the novel capacity of SIRT2 to enhance subcutaneous melanoma progression while raising the vital question of at what point does SIRT2, a tumor suppressor protein that promotes genomic integrity in healthy cells, transition into what can only be described as a tumor promoter.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that G1 phase cell cycle arrest is associated with the inhibition of SIRT2 expression. 17 Fluorescence microscopy demonstrated that Gs-Rg3 decreased SIRT2 levels in a dose-dependent manner (Figure 4(A)), which was confirmed through Western blot analysis. Furthermore, Gs-Rg3mediated SIRT2 level reductions increased the global cellular acetylation of H3K18 and H4K16 (Figure 4(B) and (C)), indicating that Gs-Rg3 suppresses SIRT2 levels and promotes the acetylation of SIRT2 target sites, thereby regulating the HCC (Bel-7402 and HCCLM3) cell cycle and proliferation.…”
Section: Exposure To Gs-rg3 Decreases Sirt2 Levels Concomitant With Increased Histone Acetylationmentioning
confidence: 66%
“…Currently, the literature supports diverging functions for SIRT2 in tumorigenesis, in a context-dependent manner, that act to modify epigenetic pathways implicated in cancer's initiation, promotion, and progression [38][39][40]. Our ndings illustrate the novel capacity of SIRT2 to enhance subcutaneous melanoma progression while raising the vital question of at what point does SIRT2, a protein that promotes genomic integrity in healthy cells, transition into what can only be described as a cancer promoter.…”
Section: Discussionmentioning
confidence: 77%